Spree - Kotlyarenko, Eugene; Keery, Joe; Zamata, Sasheer, 1986-; Barton, Mischa; DeLuca, John; Mooney, Kyle; Arquette, David ([United States] : Rlje Films, 2020)
Kurt dreams of sitting atop a social media empire, but for now, he drives for the rideshare company Spree. Fortunately, Kurt has come up with the perfect way to go viral: #TheLesson. He's decked out his car with cameras for a nonstop live stream full of killer entertainment, murdering his passengers. In the middle of all this madness, a stand-up comedian with her viral agenda crosses Kurt's path and becomes the only hope to put an end to his misguided carnage.
Special features: director audio commentary; kurtsworld96 social media content.
Director, Eugene Kotlyarenko.
Joe Keery, Sasheer Zamata, Mischa Barton, John Deluca, Kyle Mooney, David Arquette.
DVD, NTSC; Dolby digital 5.1; widescreen (1.78:1).
English audio; English, French, Spanish subtitles.
English subtitles for the deaf and hard of hearing.
Keywords: Social media -- Drama; Serial murderers -- Drama